Factors Influencing Labor Absorption in the Agricultural Sector in Central Kalimantan Province - Ririanti Ririanti; Muhammad Fauzi; Sadik Ikhsan (Universitas KH. Abdul Chalim Mojokerto, 2025)
The research objectives are 1) to describe the development of the agricultural sector workforce, regional minimum wage (UMR), gross regional domestic product (GRDP) and agricultural land area in Central Kalimantan Province by district/city in 2017-2022; 2) to analyze the influence of regional minimum wage (UMR), gross regional domestic product (GRDP) and agricultural land area on the absorption of agricultural sector workforce in Central Kalimantan Province in 2017-2022. This research method employs panel data regression analysis and secondary data collected by the Central Kalimantan Central Statistics Agency from 2017 to 2022. The analysis tool used is EViews 12. The results of the study show that the development of the workforce, UMR, GRDP, and agricultural land area in Central Kalimantan Province from 2017 to 2022 exhibited various dynamics, with each indicator displaying trends and fluctuations that reflect socio-economic conditions and policies at both the district/city level and the provincial level. Factors that influence the absorption of labor in the agricultural sector in Central Kalimantan Province based on the results of panel data regression analysis using the Fixed Effect Model are UMR which has a negative coefficient value of -0.000914, GRDP has a positive coefficient value of 3.477186 and agricultural land area which also has a positive coefficient value of 0.001264 with an R-square value obtained of 97.25% which shows that variations in labor absorption in the agricultural sector can be explained by the independent variables included in the model.